The Adaptation of Management Consultant Profession from International Trends to Romanian Market Conditions - Felix Angel Popescu; Laurențiu Petrila (Agora International Journal of Economical Sciences (AIJES), 2017)
As a point of reference on the Romanian market for management consulting services, it can be stated that its evolution over the last years has suffered a positive impact, in principle, due to the relative overcoming of the period of economic recession. Of course, this does not mean that the situation of client companies is extremely favorable, because it is precisely this period of return and re-adjustment to market requirements that has led to cost cutting measures, including management consulting costs.
Keywords: 330